Pelanggaran Penggunaan Prinsip Kesantunan Berbahasa dalam Drama Komedi Lapor Pak di Trans 7 - Dora Zulkarniah; Novia Juita (Persona: Kajian Bahasa dan Sastra, 2023)
This article aims to describe violations of the principles of linguistic politeness in the comedy drama Lapor Pak in Trans 7. This research is a qualitative linguistic research with descriptive methods by describing the data found to obtain general conclusions. The data used in this research is in the form of speeches from actors in the comedy drama sketch Lapor Pak. Data collection was carried out by: (a) watching video replays on YouTube (b) then transcribing them from oral to written form (c) classifying speech in table format (d) identifying speech formats that violate the six maxims according to Geoffrey Leech. The results of this research show that: 136 types of violations of the principle of wisdom were found, violations of the principle of praise were 162 statements, violations of the principle of humility were 14 statements, and violations of the maxim of sympathy were 34 statements. The Principle of Generosity is not found.